Optical Processes in Microparticles and Nanostructures : a Festschrift Dedicated to Richard Kounai Chang on His Retirement from Yale University. - Serpenguzel, Ali (World Scientific, 2010)
This Festschrift is a tribute to the eminent scholar, Professor Richard Kounai Chang, on his retirement from Yale University on June 12, 2008. During his over four decades of scientific exploration, Professor Chang has made a lasting contribution to the development of linear and nonlinear optics and devices in confined geometries, of surface second-harmonic generation and surface-enhanced Roman scattering, and of novel methods for detecting airborne aerosol pathogens. This volume assembles a collection of articles contributed by former students, collaborators, and colleagues of Professor Chang.